Perancangan Solar Tracker Dual Axis untuk Optimasi Panel Surya - Any Kurniawaty Yapie; Fathur Riski (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
in this global era, the development of renewable energy is the main focus to reduce dependence on fossil fuels and negative impacts on the environment. Solar energy is one of the most promising renewable energy sources on this earth of Indonesia, which can be harvested through solar panels. This study aims to design and create a dual-axis solar tracker prototype using an Arduino Uno microcontroller to increase the absorption of solar energy by solar panels. This prototype uses an LDR sensor and a servo motor to move the solar panel following the movement of the sun throughout the day. The test results show that the use of a solar tracker system can increase the power generated by solar panels in the morning and evening, thereby reducing the difference in power generated in the morning-evening and afternoon.